Political Dynamics the Rift of EPRDF Coalitions Since the Outbreak of Qerros Protest to the Nomination of Dr. Abiy Ahmed in Ethiopia - Dame Dereba Shoa; Hana Mekonen Gizaw (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2021)
Ethiopia has been under the rule of EPRDF coalitions, a vanguard party ruling the country since the collapse of Derg regime. This article is therefore, intended to explore the political dynamics associated with the rift of EPRDF coalitions since the outbreaks of Qerros protest. To meet the study purposes, qualitative research design was employed to collect the data. The study reveals that the broke out of Qerros protest against integrated master plan of Addis Ababa and tyrannical rule of EPRDF used to be the key dawn towards the step down of titular OPDO officials and empowerment of reformist ODP officials in place that eventually split ruling coalitions in to conservative and reformist. Broad spectrum of political dynamics like: declaration of state of emergency, massive displacement of Oromo people from Ethio-Somali region, wider public protests accompanied by sectorial boycotts, political unrest, apprehension of contrabandist, resignation of late prime minister, Mr. Hailemariam Desalegn and nomination of Dr. Abiy Ahmed in place and others were ensued from the rift of ruling coalitions. The study implicate that polarized political interests amidst the ruling parties (TPLF and PP) could be extended to the oppositions and wider people that may escalate ethnic tensions and thereby ensue in the state fragility.